Still as divided as ever? Northern Ireland, football and identity 20 years after the Good Friday Agreement. (17th November 2019) - Hassan, David; Ferguson, Kyle
ABSTRACT: The signing of the Belfast-Good Friday Agreement in 1998 was widely welcomed by those that interpreted it as offering Northern Ireland the prospect of a fresh start, free from inter-ethnic violence that had blighted the country for almost 80 years. Soon it began to be seen by some observers as the genesis too of a 'Northern Irish' identity, as the community at large came to reconcile themselves to their common lives in Northern Ireland. Sport was also viewed as offering the prospect of adding weight to this sense of a shared journey and governing bodies of sport unquestionably played their parts in supporting a settled political environment where division had previously existed. This article examines the still contested concept of a 'Northern Irish' identity and critically reviews its real currency in a divided society, even if sport and, specifically, association football offers renewed hope for something better in the time ahead.